Effect of stream segregation on ozonation for the removal of significant COD fractions from textile wastewater - Doǧruel, Serdar; Germirli‐Babuna, Fatoş; Kabdaşlı, Işık; Insel, Güçlü; Orhon, Derin (Wiley, 2002)
AbstractOzonation was tested on selected streams of cotton finishing textile plant wastewater for optimizing chemical oxygen demand (COD) removal. For this purpose, significant COD fractions in the wastewater were experimentally identified and the effect of ozone on these fractions was investigated. Ozonation experiments were performed with a 1 dm3 sample volume. Ozone treatment of batches of raw wastewater provided, at a rate of 62 mg min−1 and a gas feeding time of 15 min, achieved complete colour removal but only 21% COD reduction. Increasing the feeding time to 30 min slightly increased the COD removal to 32%. At this feeding time, removal of the readily biodegradable COD was 60%, but soluble inert COD reduction remained at 16%, indicating selective preference of ozone for simpler compounds. At low concentrations, ozone was mainly influential on soluble COD compounds. Longer feeding times also affected particulate compounds, resulting in the solubilization of the COD fractions. Pre‐ozonation of the dye‐house wastewater, as a segregated stream, proved much more effective in the breakdown of refractory organic compounds, rendering the overall plant effluent more amenable to biological treatment.© 2002 Society of Chemical Industry